Highly enantioselective and diastereoselective conjugate addition of 5H-oxazol-4-ones to 2-chloroacrylonitrile catalyzed by chiral guanidines. Issue 36 (2nd September 2015) - Misaki, Tomonori; Choi, Na-Rae; Morita, Akane; Sugimura, Takashi
Graphical abstract: Abstract: The chiral guanidine-catalyzed conjugate addition of 5 H -oxazol-4-ones to 2-chloroacrylonitrile was developed with high enantiomeric and diastereomeric control. Introduction of an electron-donating 4-methoxyphenyl group as an aromatic substituent (Ar) on 5 H -oxazol-4-one was suitable for inhibiting undesirable cyclization and achieving high stereoselectivity in this conjugate addition. The derivatization of an obtained product was also performed to afford a chiral α-siloxyimide, which was subsequently converted to the corresponding α-siloxy-γ-lactam in a few steps.